Perceived ease of use of ict by healthcare staffs' in western region of sri lanka - Dileep, A.H.; Wijayanayake, W.M. J. I. (University of Jaffna, 2016)
Information and Communication Technology for health and well being is becoming increasingly important to deliver top-quality care to people. Healthcare staffs are change agents in healthcare sector. They are key drivers who play crucial role in ICT integration in healthcare. The aim of this study is to examine healthcare staff level of ease of use towards ICT in western region of Sri Lanka. A sample of 100 healthcare staff was assessed for their ease of use towards ICT using a Likert type questionnaire (Strongly Disagree (SD), disagree (D), Neutral (N), Agree (A), Strongly Agree (SA)) and Statistical Package for the Social Science (SPSS). There were 60 females (60%) participants and 40 were male (40%). The average number of years of computer use was 8.73 years (SD=5.722). There were negative responses (SD - 11%, D - 53%) for reverse scoring question. Further, there were positive responses (SA 12%, A 54%, N 23%) for positive scoring questions. The healthcare staffs in western region of Sri Lanka have positive comfort level towards ICT. They are comfortable to work with computerized environment. This study clearly shows that healthcare staff comfort level towards ICT are high and that strengthen the integration of ICT to the State hospitals in western region of Sri Lanka.
Keywords: Ehealth; ICT for healthcare; ICT adaption for hospital; Healthcare staff attitude for ICT